2005
DOI: 10.1021/jf050065r
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Analytical Methodology for Determination of Oxytetracycline and Tetracycline Residues in Honey by HPLC with Fluorescence Detection

Abstract: An analytical method for the determination of OTC and TC residues in honey was developed. Sample treatment involves an extraction in EDTA-McIlvaine buffer, followed by a solid-phase cleanup step. With regard to the cleanup procedure, different SPE cartridges were evaluated and the results presented. The method was validated according to the guidelines laid down by the 2002/657/EC European Decision parameters: decision limit (Cc alpha) and detection capability (CC beta) were 20 and 21 microg/Kg and 49 and 50 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 10 publications
0
56
0
7
Order By: Relevance
“…However, Pena et al found that COOH treatment was not suitable or stable for several honeys due to the large variation in the pH in the extracts. They recommended propylsulfonate (PRS) cartridge treatment, which was not a#ected by pH because of its strong cationic exchange characteristics 13) . We confirmed the e#ectiveness of PRS on some dark-colored honeys, but it was ine#ective on buckwheat honey.…”
Section: Clean-up Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pena et al found that COOH treatment was not suitable or stable for several honeys due to the large variation in the pH in the extracts. They recommended propylsulfonate (PRS) cartridge treatment, which was not a#ected by pH because of its strong cationic exchange characteristics 13) . We confirmed the e#ectiveness of PRS on some dark-colored honeys, but it was ine#ective on buckwheat honey.…”
Section: Clean-up Proceduresmentioning
confidence: 99%
“…However, the above methodology could not be used for certain honeys because of their strong matrix e#ects. To remove matrix e#ects of dark-colored honeys, a more rigorous clean-up procedure is required 4), 8), 13) . Although metal chelate a$nity chromatography (MCAC) has been reported as an e#ective purification technique of TCs in livestock products 18)ῌ22) , MCAC cleanup could not solve the problem of matrix e#ects from bee-related products for the following reason.…”
Section: Introductionmentioning
confidence: 99%
“…(UV), 9,10 fluorescence, 14,15 chemiluminescence 16 and mass antibiotics, which are commonly used in veterinary medicine to spectrometry. [17][18][19] One major obstacle in the detection of TCs prevent diseases and also to promote growth, 1 takes a central by HPLC is the presence of impurities in honey.…”
Section: Introductionmentioning
confidence: 99%
“…These include: microbiological assay (Nagel et al 2011), differential scanning calorimetry (DSC) (Yildiz and Unluturk 2009), capillary electrophoresis (CE) (Ibarra et al 2011), enzyme-linked immunosorbent assays (ELISA), radioimmunoassays, biosensors and chromatographic techniques, such as high-performance liquid chromatography (HPLC), coupled with different detection systems (Toldrá and Reig 2006), liquid chromatography operating under reverse phase mode (Aderson et al 2005) and coupled with several detection schemes such as spectrophotometry (Viñas et al 2004;Andersen et al 2005;Fritz and Zuo 2007), electrochemical (Casella and Picerno 2009), fluorescence (Pena et al 2005;Pena et al 2007;Schneider et al 2007), or mass spectrometry (Andersen et al 2005;Pena et al 2007), among others.…”
mentioning
confidence: 99%